Preparation of Ta2O5 nanoparticles by using cathode glow discharge electrolysis. (15th December 2021) - Lu, Quan-Fang; Li, Juan-Long; Yu, Jie; Cui, Li-Juan; Wang, Bo; Ma, Xiao-Juan; Feng, Yan
Abstract: Tantalum pentoxide nanoparticles (Ta2 O5 NPs) were fabricated by cathode glow discharge electrolysis (CGDE) generated between a needle-like platinum wire cathode and a tantalum foil anode in 6 g L −1 Na2 SO4 electrolyte solution containing 5 ml hydrofluoric acid (HF) and 0.075 g cetyltrimethyl ammonium bromide (CTAB). The chemical structure, composition and morphology of the obtained powder were analyzed by using XRD, FT-IR, SEM/EDS, XPS and UV–vis DRS. The results found that Ta2 O5 NPs with orthorhombic structure and wide band gap (3.6 eV) are successfully fabricated at 500 V discharge voltage in about 3 h. CTAB as a stabilizing agent can reduce the agglomeration due to forming CTA + and attaching the surface of the synthetic products. A possible preparation mechanism of Ta2 O5 NPs is proposed. Firstly, the tantalum foil anode is oxidized to form a compact Ta2 O5 layer. Then, Ta2 O5 surface is etched to form soluble [TaF7 ] 2− complexes in the presence of HF. After that, soluble [TaF7 ] 2− complexes can react with H2 O to form Ta(OH)5 . Finally, Ta(OH)5 is further converted to Ta2 O5 from plasma-liquid interface into solution.